2015
DOI: 10.1126/science.aaa7055
|View full text |Cite
|
Sign up to set email alerts
|

Chiral solitons in a coupled double Peierls chain

Abstract: Chiral edge states are the hallmark of two- and three-dimensional topological materials, but their one-dimensional (1D) analog has not yet been found. We report that the 1D topological edge states, solitons, of the charge density wave system of indium atomic wires self-assembled on a silicon surface have chirality. The system is described by a coupled double Peierls-dimerized atomic chain, where the interchain coupling induces dynamical sublattice symmetry breaking. This changes its topological symmetry from Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
139
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 31 publications
5
139
1
1
Order By: Relevance
“…The prototype of its realization is the one based on the Su-SchriefferHeeger/Rice-Mele (SSH/RM) model [22,23] for polyacetylene. It has generated renewed interests thanks to various recent experimental realizations in ultracold atoms and condensed matter systems, where the Zak phase [24], quantum pumping phenomena [25][26][27], and chiral solitonic edge states [28] are directly measured. In this Letter, we present a generalized Creutz scheme [29] as a distinct microscopic two-band quantum pump model utilizing quantum interference effect.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…The prototype of its realization is the one based on the Su-SchriefferHeeger/Rice-Mele (SSH/RM) model [22,23] for polyacetylene. It has generated renewed interests thanks to various recent experimental realizations in ultracold atoms and condensed matter systems, where the Zak phase [24], quantum pumping phenomena [25][26][27], and chiral solitonic edge states [28] are directly measured. In this Letter, we present a generalized Creutz scheme [29] as a distinct microscopic two-band quantum pump model utilizing quantum interference effect.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…The next step is logic or algebraic operations of such topological bits [20][21][22] . Here, we show experimentally the switching between chiral topological excitations or chiral solitons of di erent chirality in a one-dimensional electronic system with Z 4 topological symmetry 23,24 . We found that a fast-moving achiral soliton merges with chiral solitons to switch their handedness.…”
mentioning
confidence: 97%
“…The electronic states of RC (LC) solitons emerge below (above) the Fermi level within the bandgap, whereas AC solitons have their states both above and below the Fermi level ( Supplementary Fig. 2a) 23,24 . The electronic difference results in the fact that RC solitons always looks brighter in STM images than LC solitons due to their enhanced density of states in filled states ( Supplementary Fig.…”
mentioning
confidence: 99%
“…A 1D CDW is a macroscopic quantum state, where atoms in a 1D metallic system relax and break translational symmetry to reduce total energy by opening a small bandgap at the Fermi energy (E F ) and modulating the charge density at the periodicity of the lattice distortion 30,31 . Although CDW order has been observed in 2D TMD metals such as NbSe 2 and TiSe 2 at low temperature 32,33 , CDWs have not previously been associated with 2D TMD semiconductors.Most studies of 1D CDWs have been performed on ensembles of CDWs in conducting polymers, quasi-one-dimensional metals or self-assembled atomic chains adsorbed on semiconducting surfaces, where inter-CDW coupling can significantly impact CDW properties [34][35][36][37][38] . The CDWs observed here are electronically isolated from one another, and have truly one-dimensional character, forming an atomically precise model system to explore intrinsic CDW phenomena.…”
mentioning
confidence: 99%